Syntaxonomy of weed vegetation of crops cultures of the Crimea (CHORNOMORSKI BOTANICAL JOURNAL, 2005)
Critical review of classification of weed vegetation of crops cultures of the Crimea is presented. It includes 19 associations, 8 alliances, 4 orders of class Stellarietea mediae according to Braun-Blanquet system. Phytocoenological characteristic of syntaxons, their diagnostical species have been revealed. The features of zonal distributional of communities in various agrocoenoses are considered.
Keywords: syntaxonomy, segetal vegetation, crops, Crimea.